Working hour arrangements and working hours: A microeconometric analysis based on German time diary data - Joachim Merz; Derik Burgert (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2003)
The labour market providing individual resources and economic well-being is still a topic in the economic and social policy discussion. In the course of time the traditional full-time work is diminishing, new labour arrangements are discussed (keyword: flexible labour markets). This study will contribute to the discussion of working hour arrangements by quantifying patterns of explanation of who is working when within a workday. In particular we want to disentangle certain working hour patterns and the final hours of work according to those different patterns allowing for market and non-market influences. The daily working hour patterns are analysed by two dimensions: the fragmentation of a working day (by the number of working episodes) and the timing of work time by location of those episodes within the day's period. Deducting such patterns allows not only to describe possible workday interruptions and workday behaviour in general, but to give hints for which groups of the society non-traditional working time is important. Once quantified, labour market policy has a sound base for a targeted policy. Our model is based on a microeconomic labour supply approach, however extended by two dimensions: first, by daily working time arrangements with focus on core and non-core working time crossed by number of episodes and, second, by labour supply factors in a market and non-market context. Our microeconometric estimates use a multinomial logit (MNL) model to explain the working hour arrangement probability and a MNL selectivity bias corrected hours estimation for arrangement specific working hours with correct asymptotic covariances. Our study is the first German study of this kind which could analyse the actual available German Time Use Survey 1991/92 from the Federal Statistical Office with ca. 32.000 time diaries. – – Der Arbeitsmarkt als Quelle wirtschaftlichen Wohlstands steht weiterhin in der öffentlichen Debatte zur Wirtschafts- und Sozialpolitik. In jüngster Zeit, in der der traditionelle Vollzeitarbeitsplatz an Bedeutung verliert, werden insbesondere neue Formen der Arbeitszeitgestaltung diskutiert (Stichwort: flexible Arbeitsmärkte).Die vorliegende Arbeit trägt zur Diskussion solcher Arbeitszeitarrangements bei, indem Modelle quantifiziert werden, die die Frage klären: Wer arbeitet zu welcher Tageszeit? Insbesondere wollen wir marktmäßige und nicht-marktmäßige Einflüsse auf die Wahl bestimmter Muster von Arbeitszeit und der Länge der täglichen Arbeitszeit bestimmen. Die Arbeitszeitmuster untersuchen wir hinsichtlich zweier Dimensionen: der Zerstückelung des Arbeitstages in mehrere Episoden von Arbeit und der zeitlichen Lage dieser Episoden. Mit der Identifizierung der Arbeitszeitmuster lässt sich auch herausfinden, für welche sozialen Gruppen nicht tradierte Arbeitszeiten von Bedeutung sind. Diese quantitativen Auswertungen bieten der Arbeitsmarktpolitik eine Grundlage für eine zielgerichtete Politik.Unser Modell basiert auf einem mikroökonomischen Arbeitsangebotsansatz erweitert um zwei Dimensionen:: einerseits um die Muster täglicher Arbeitszeit, andererseits um Arbeitsangebotsfaktoren im Kontext marktmäßiger und nicht-marktmäßiger Aktivitäten. In unseren mikroökonometrischen Schätzungen verwenden wir ein multinomiales Logit (MNL) zur Erklärung der Wahrscheinlichkeit, ein bestimmtes Arbeitszeitmuster zu wählen, und eine MNL-selektionskorrigierte Schätzung der Arbeitszeit mit der dazugehörigen asymptotischen Kovarianzmatrix. Unsere Studie ist die erste dieser Art, die die aktuell zugänglichen deutschen Zeitverwendungserhebung 1991/92 des Statistischen Bundesamtes mit ihren 32000 Zeittagebüchern auswertet.
Keywords: J22; J23; 330; Working hour arrangements; timing of work time; working hours; German time budget stud; time use diary data; dicrete/continous extended labour supply modelling and MNL/COLS-estimation; Arbeitszeitarrangements; Arbeitsstunden; Deutsche Zeitbudgeterhebung; Zeittagebücher; diskret-kontinuierliche erweiterte Arbeitsangebotsmodellierung und MNL/COLS-Schätzung; Arbeitszeitgestaltung; Zeitverwendung; Haushaltsökonomik; Schätzung; Deutschland